Cefazolin-containing poly(ε-caprolactone) sponge pad to reduce pin tract infection rate in rabbits - Hirotaka Mutsuzaki; Ayako Oyane; Yu Sogo; Masataka Sakane; Atsuo Ito (Elsevier, 2014)
In our previous study, a fibroblast growth factor-2 (FGF-2)-apatite composite layer coated on titanium screws effectively prevented pin tract infection in rabbits because of enhanced wound healing; however, the FGF-2-apatite composite layers did not completely prevent pin tract infection. Thus, we recently developed a poly(ε-caprolactone) (PCL) sponge pad embedded with cefazolin sodium (+CEZ), which has a fast-acting bactericidal effect. The pad is placed on the skin around the screws. The purpose of this study was to determine the anti-infective efficacy of the +CEZ pad on the pin-skin interface of the FGF-2-apatite-coated titanium screws. The +CEZ pads were prepared by mixing PCL and CEZ in 1,4-dioxane, followed by freeze-drying and compaction. They were analyzed regarding their surface structure, in vitro CEZ release profile, and bactericidal activity. The FGF-2-apatite-coated screws were implanted percutaneously in bilateral rabbit proximal tibial metaphyses-with and without the +CEZ pad-for 4 weeks (n = 20). The + CEZ pads consisted of a porous matrix of PCL in which CEZ was embedded. The CEZ-release profile showed an initial burst on Day 1 and a sustained release lasting for 30 days. The +CEZ pad retained its bactericidal activity against Staphylococcus aureus after preincubation on an agar plate for 7 days. Based on visual inspection, the pin tract infection rate was successfully reduced from 72.2% to 15.0% with the +CEZ pad (p < 0.05), which reduced the bacterial count, especially S. aureus (p < 0.05). The histological inflammation rate of the soft tissues was also significantly lower with the +CEZ pad than without it (p < 0.05). The pin tract infection rate was reduced to one-fifth with the +CEZ pad. Using it as described improves infection resistance during percutaneous implantation.